Panel regression method to analyse stock market returns during covid-19 / Nur Mardziah Aziz Jaafar - Aziz Jaafar, Nur Mardziah (2021)
Malaysia's earliest COVID-19 patients, reported on January 25, 2020, were travellers from China to Malaysia through Singapore. However, small number of confirmed cases were detected before March 2020. There was a religious gathering in a mosque in February 2020 due to which many positive cases were reported in the next month. Consequently, the Prime Minister of Malaysia called for the 'Movement Control Order' as of March 18, 2020. This study aimed to determine the aftereffects of COVID-19 outbreaks on stock market during the pandemic. It attempted to determine the correlation between market returns and daily growth of total new and death cases of COVID-19. To achieve the study's objective, this research has implemented the Panel Regression Method, Pooled Ordinary Least Square and fixed-effect method to analyse the daily growth of new confirmed cases and death cases of COVID-19. Using the data of the new and death cases of COVID-19 outbreak in Malaysia, the results show that the stock market returns were negative and had a significant relationship to both total new cases and death cases' daily growth since the p-value is less than 0.1, 0.05, and 0.01. The findings also indicated that all the stock market sector indices were badly affected by the COVID-19. Besides helping investors make the right decision during a pandemic crisis, the findings can be expanded, in future research, by increasing the data frame, independent variables and finding the impact of the more specific indices of the sector.